Julius Malema, from Masupatsela to the Formation of the Economic Freedom Fighters (EFF): Historical Narrative - Soldaat, Mohau (African historical review, 2024)
Julius Malema was born in 1981 during the apartheid era in South Africa and began his political journey at an early age. As he rose in the political space, he became prominent, playing a critical role in reviving the African National Congress Youth League (ANCYL). He was exposed to formal politics from the age of nine when he joined Masupatsela (Trailblazers), the youth brigade of the African National Congress (ANC) at the time. He rose to positions of power through joining the ranks of the Congress of South African Students (COSAS), the ANCYL, and post his expulsion from the ANCYL, established his own organisation, the Economic Freedom Fighters (EFF), of which he is the current president, also known as the commander in chief (CiC). The article interrogates Malema's role in South African politics, and how he contributed to growing factionalism in the ANC. First, the article discusses Malema's early stages of joining politics, and his gradual growth, until he became the president of the ANCYL in 2008. Second, the article discusses his role in the politics of the mother body, the ANC, that is, in policies. Third, the article scrutinise why Malema was expelled from the ANCYL and, last, the emergence of the EFF in 2013 and its radical stance in the politics of South Africa.